Endoscopic ultrasound-guided biliary drainage using a lumen-apposing self-expanding metal stent: a case series - Brückner, Stefan; Arlt, Alexander; Hampe, Jochen (Endoscopy, 2015)
Endoscopic ultrasound-guided biliary drainage (EUS-BD) might be an alternative to percutaneous or transpapillary biliary drainage in unresectable pancreatic or biliary cancer. A lumen-apposing, fully covered, self-expanding metal stent, which creates a sealed transluminal conduit between the biliary and gastrointestinal tract may offer advantages over conventional plastic and metal stents. In this retrospective, observational, open-label case study, five patients underwent EUS-BD for obstructive jaundice in pancreatic cancer (n = 4) or distal cholangiocarcinoma (n = 1). Technical and functional success was achieved in all patients without complications. The development of specialized stent and delivery systems may render EUS-BD an effective and safe alternative to percutaneous or transpapillary approaches.